An exploratory study of the experiences of black teenage mothers - Mpetshwa, Nomonde (Rhodes University, Faculty of Humanities, Department of Social Work, 2001)
An exploratory descriptive design was used to explore the experiences of a sample of black teenage mothers of Libode, Ngqeleni and Port St Johns. A St Barnabas Hospital birth record register was used to select seven Xhosa speaking black teenage mothers, with children under a year old who have kept their children and are staying with their extended families. Qualitative interview was used to collect data from the abovementioned respondents. The data one want to use may not feasibly be available in any other form, so that asking people for their accounts, talking and listening to them, may be the only way to get at what you are interested in (Mason 1998:39). Qualitative interview was therefore used to collect data from the abovementioned respondents. Qualitative interview according to Mason (1998:38) involve one to one interaction as in this study, or a larger group, and it carries more advantages in data collection compared to other research tools. Some interesting information, which drew the researcher's attention, was gathered. Information such as the reaction by family members, community and its structures, and peers including teenage fathers, made the research more challenging. The anger showed by brothers of one of respondents raised the researcher's curiosity. Another interesting piece of information that was gathered was the negative reaction by the church. The researcher had no idea that the church can negatively involve itself in community affairs, but one of the respondents reported to have been encouraged by one of the church members to go on with her studies despite her pregnancy. The same applied to some schools, where pregnant teenagers were not allowed to continue schooling, while in other schools the same situation was allowed. The major findings were that, respondents have forfeited some of their favorite hobbies such as extra mural school activities, teenage activities and their lives have been negatively affected by their teenage motherhood in areas such as education, family relations, peer relations including their boyfriends and community. Again lack of support by people close to these young mothers including different professionals has also been identified. It has also transpired during this study that, teenagers can indeed be good mothers, but socioeconomic stress and lack of social support often prevent them from giving their babies a reasonable start in life. Amongst the recommendations made undertaking a bigger study has been suggested
Keywords: Teenage pregnancy; Teenage pregnancy -- South Africa -- Eastern Cape; Black teenage mothers -- South Africa -- Eastern Cape